THE EFFECT OF PROJECT IN PROBLEM-BASED LEARNING ON STUDENTS' SCIENTIFIC AND INFORMATION LITERACY IN LEARNING HUMAN EXCRETORY SYSTEM - Siti Juleha, - (2018)
The present study aims to investigate the effect of Project in Problem-Based Learning on students' scientific and information literacy in grade 8 studying in one of the private schools in Bandung in learning the human excretory system. A sample of 39 students in two classes was selected purposively from five classes available in the school. An experimental group comprising 19 students received the instruction by Problem-Based Learning with the final assessment of creating an article project while the control group comprising 20 students received the human excretory instruction by using Problem-Based Learning without Project in the final assessment. The data was administered via the pre-test and post-test. The results were statistically analyzed using SPSS software by employing an independent t-test. Results indicated that after the one-month treatment period, students in the experimental group have a higher score in the scientific literacy test compared to the students in the control group even it was not significantly different. Therefore, the results of students' information literacy showed that there was a significant difference between the experiment and control group. It is concluded that the project in problem-based learning is useful to be conducted as the learning strategies in the classroom to improve students' scientific and information literacy.;--Penelitian ini bertujuan untuk menginvestigasi efek proyek dalam pembelajaran berbasis masalah terhadap literasi sains dan informasi siswa kelas 8 di salah satu sekolah swasta di Bandung dalam topik sistem eksresi pada manusia. Sejumlah 39 sampel siswa yang terdapat di dalam dua kelas dari total lima kelas dipilih secara purposif. Kelas eksperimen terdiri dari 19 siswa menerima pembelajaran berbasis masalah (PBL) dengan projek artikel sebagai tugas akhir. Sedangkan kelas kontrol terdiri dari 20 siswa menerima pembelajaran sistem ekskresi pada manusia dengan menggunakan pembelajaran berbasis masalah tanpa diiringi tugas akhir pembuatan projek artikel. Data kemudian dikumpulkan melalui pre-tes dan pos-tes. Hasil dari data tersebut kemudian diuji menggunakan t-test pada program perangkat lunak SPSS. Berdasarkan analisis data didapatkan bahwa kelas eksperimen mendapatkan nilai yang lebih tinggi pada tes literasi sains daripada kelas kontrol walaupun hasilnya tidak signifikan. Sedangkan pada tes literasi informasi, terdapat perbedaan yang signnifikan antara kelas eksperimen dan kelas kontrol. Hal ini menyimpulkan bahwa proyek dalam pembelajaran berbasis masalah dapat diimplementasikan pada pembelajaran di dalam kelas guna meningkatkan literasi sains dan informasi siswa.